2017
DOI: 10.3390/ma10030281
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution of TiC Particles In Situ, Synthesized by Laser Cladding

Abstract: In this paper, a TiC reinforcement metal matrix composite coating is produced using nickel and graphite mixing powder on the surface ofTi-6Al-4V alloy by laser radiation. The microstructure of the coatings is investigated by XRD, SEM and EDS. Results show that most of the TiC phase is granular, with a size of several micrometers, and a few of the TiC phases are petals or flakes. At the cross-section of the coatings, a few special TiC patterns are found and these TiC patterns do not always occur at the observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Metal matrix composites (MMCs) are outstanding materials bilaterally benefitting from the properties of at least two constituents: the metal matrix (usually an alloy), and the reinforcement (in general, an oxide, an intermetallic compound, a carbide or a nitride) [1,2,3]. Incorporation of reinforcements into the metallic matrix is generally associated with the improvement in hardness, specific strength, wear resistance, fracture toughness, and stiffness compared to the monolithic counterparts [4,5,6,7]. Owing to their desired structural and functional properties, MMCs have found their application in numerous technological fields including automotive, aerospace and biomedical industries [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Metal matrix composites (MMCs) are outstanding materials bilaterally benefitting from the properties of at least two constituents: the metal matrix (usually an alloy), and the reinforcement (in general, an oxide, an intermetallic compound, a carbide or a nitride) [1,2,3]. Incorporation of reinforcements into the metallic matrix is generally associated with the improvement in hardness, specific strength, wear resistance, fracture toughness, and stiffness compared to the monolithic counterparts [4,5,6,7]. Owing to their desired structural and functional properties, MMCs have found their application in numerous technological fields including automotive, aerospace and biomedical industries [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al produced a TiC enhanced nickel-based composite coating. They concluded that the phase and distribution of TiC were affected by convection in the molten pool [ 14 ]. Saroj et al created a TiC-Inconel 825 composite coating employing a Tungsten Inert Gas (TIG) cladding method and discovered the impact of different TiC percentages (20%, 40%, and 60%) and processing currents on the coating morphology, micro-hardness, and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As one approach for producing TMCs, in situ synthesis techniques have drawn extensive interest because of their superior properties along with the ease of fabrication [5][6][7]. Among the reinforcements available for TMCs, TiB whiskers (TiB w ) and TiC particles (TiC p ) are the most suitable reinforcements since they possess high thermal stability, similar density and thermal expansion coefficient to titanium alloys, high modulus and stiffness [8][9][10].…”
Section: Introductionmentioning
confidence: 99%